1999
DOI: 10.1677/jme.0.0230199
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin is expressed in the anterior and intermediate lobes, but not in the posterior pituitary of sheep

Abstract: We have examined the expression of the ovine clusterin gene in the sheep pituitary gland, with the aim of determining its site of synthesis in this tissue. Northern blotting analysis of extracted polyadenylated RNA, using a 32 P-labelled rat clusterin cDNA probe, detected the greatest amounts of clusterin mRNA in the anterior part of dissected pituitary glands. In situ hybridisation studies showed clusterin mRNA in anterior and intermediate Journal of Molecular Endocrinology (1999) 23, 199-208 INTRODUCTIONClu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Hence, like bovine pituitary, the role of colloid as the transport medium from the pituitary to any extra pituitary is not convincing. Recent identification of clusterin, the glycoprotein component of the colloid [Ogawa et al, 1997;Fleming et al, 1999], was suggested to be the deposition due to phagocytotic activity of folliculo-stellate cells [Inoue et al, 2002]. In the present study, the colloid of the follicular lumen may be comprised of secretion of agranular stellate cells and endocrine cells rather than cell fragmentation or degeneration products, as also suggested by Azzali et al [2003].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Hence, like bovine pituitary, the role of colloid as the transport medium from the pituitary to any extra pituitary is not convincing. Recent identification of clusterin, the glycoprotein component of the colloid [Ogawa et al, 1997;Fleming et al, 1999], was suggested to be the deposition due to phagocytotic activity of folliculo-stellate cells [Inoue et al, 2002]. In the present study, the colloid of the follicular lumen may be comprised of secretion of agranular stellate cells and endocrine cells rather than cell fragmentation or degeneration products, as also suggested by Azzali et al [2003].…”
Section: Discussionsupporting
confidence: 72%
“…These structures were named epithelial cysts [Benjamin, 1981;Kameda, 1991;Watanabe, 1991;Mohamed et al, 2000]. To understand the biological significance of extracellular accumulations in the pituitary gland, currently a few studies have been carried out employing conventional histochemical, biochemical, immunocytochemical and molecular biological techniques Boyd et al, 1986;Kameda, 1991;Ogawa et al, 1996Ogawa et al, , 1997Fleming et al, 1999;Mohamed et al, 2000;Inoue et al, 2002;Azzali et al, 2003]. These studies revealed the incidence of occurrence and mode of formation of colloid follicles/epithelial cysts, nature of follicle-building cells, distribution of colloid follicles/cysts in various parts of the pituitary gland and the chemical characterization of colloid.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clusterin expression has been observed in the adenophysis of humans, sheep and pig [21,22,23,24,25]. However, the effect of clusterin on neuroendocrine function has not been directly tested.…”
Section: Introductionmentioning
confidence: 99%